Investigating the risk factors for isthmocele development after cesarean deliveryAJOG Global Reports at a Glance - Masoud Saadat Fakhr, MD; Mahya Mozafari, MD; Kiana Rezvanfar, MD; Zahra Amini, MD; Koosha Amiri, MD; Reza Shah Hosseini, MD; Hengame Sarnaz, MD; Poorya Gholami, MD; Zohreh Lavasani, MD (Elsevier, 2024)
BACKGROUND: Cesarean delivery rates are increasing globally, raising concerns about associated complications such as isthmocele. Isthmoceles are pouch-like defects in the anterior uterine wall at the site of a prior cesarean delivery scar. OBJECTIVE: This study aimed to determine isthmocele prevalence, associated symptoms, and risk factors among women with a history of cesarean delivery. STUDY DESIGN: This cross-sectional study evaluated 297 women with prior cesarean delivery using transvaginal ultrasound to screen for isthmocele. Data on demographics, pregnancy details, comorbidities, and indications for cesarean delivery were collected. Isthmocele was defined sonographically as any niche or defect at the hysterotomy site. Descriptive and comparative analyses identified factors associated with isthmocele. RESULTS: Isthmocele prevalence was 65.3% (n=194). Abnormal vaginal bleeding was reported in 21.1% of participants, pelvic pain by 4.1% of participants, and both by 4.1% of participants. Compared to women without isthmocele, those with isthmocele were older (35.9 vs 31.6 years), had higher body mass index (26.8 vs 25.5 kg/m2), gravidity (1.8 vs 1.3), and parity (1.7 vs 1.2). Repeat cesarean delivery was more common (30.4% vs 12.6%) and elective cesarean delivery less common (33.5% vs 67.9%) among those with isthmocele. CONCLUSION: Over half of the women with history of cesarean delivery had an isthmocele. Abnormal bleeding was common. Advanced maternal age, obesity, repeat procedures, and certain comorbidities appear to increase risk. Further research on prevention and treatment is warranted given the high prevalence.